Comparison of physical fitness characteristics of Japanese female basketball players by playing position and competition level - Shiba, Junpei; Yamase, Hana (International Journal of Basketball Studies, 2023)
The purposes of this study were 1) to compare the physical fitness characteristics of Japanese female basketball players by position and 2) to compare the jumping ability of Japanese higher-competition and lower-competition level players. The subjects of this study were 13 Japanese female basketball players. The positions were categorized into three parts: guard for positions 1 and 2 (point guard and shooting guard), forward for positions 3 and 4 (shooting forward and power forward), and center for No. 5. The subjects were evaluated body mass, percentage of body fat, lean body mass, squat jump (SJ), countermovement jump (CMJ), rebound jump (RJ), 5m and 10m sprint, T-test, and 30-15 intermittent fitness test (30-15 IFT). This study was considered in the effect size (ES) due to the small sample size. The 90% confidence interval for ES of Hedge’s g was calculated to examine significant differences (p < 0.10). Guards were significantly higher SJ height and CMJ height than centers. Forwards had a significantly higher percentage of body fat than guards. Centers had significantly higher height, body mass, percentage of body fat, and lean body mass than guards. In addition, Centers had significantly higher lean body mass than forwards. Japanese seniors had significantly higher SJ height, CMJ height, and RJI than subjects of this study. Furthermore, Japanese U19 also had significantly higher SJ height, CMJ height, and RJI than the subjects of this study. This study showed that Japanese female basketball players differed in positional physical characteristics and competition-level jumping ability.